Elemental two-dimensional nanosheets beyond graphene. (22nd March 2017) - Kong, Xiangkai; Liu, Qiangchun; Zhang, Changlin; Peng, Zhenmeng; Chen, Qianwang
Abstract : The recent progress of elemental two-dimensional nanosheets, beyond graphene, has been summarized with the focus on their preparation and applications. Abstract : The great success of graphene has encouraged the fast development of other two-dimensional (2D) nanosheets, which have attracted extensive attention in different scientific fields encompassing field effect transistors, lithium-ion batteries, and catalysis. With atomic-scale thickness, almost all of the atoms are exposed on the surface, providing an extremely high specific surface area, in conjunction with special physical, chemical, and electronic properties, owing to the quantum confinement effects, which enable their surface phase to be as important as the bulk counterparts. In this review, we have summarized and discussed the recent advancements of 2D nanomaterials beyond graphene, with an emphasis on their basic fundamentals, preparation strategies, and applications. We believe that this review supplies critical insights for exploring and understanding 2D nanomaterials and puts forward the challenges and opportunities for further developments, such as more precise morphology control, foreign atom doping and surface modification technologies, atomic-scale characterization, and finding wide applications in many different fields.